Austrian Language Policy on the rights to mother tongue education - Hladonik Gergely; Гладоник Гергель (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. The study focuses on Austria’s key language policies and legislations that have an impact on German as a state language as well as minority languages. The Federal Constitution of Austria contains the most important regulations protecting German and minority languages. The first three articles of Austria's Constitution are critical legislations for the protection of state and minority languages. The Austrian Federal Constitution requires ethnic communities to be protected and preserved. The study then goes on to explore the primary organisations and administrations responsible for the evolution of today's Austrian language policy. The system in Austria for safeguarding and promoting minority languages is typically well-developed. Austria has been an active participant in European programmes aimed at the protection of minorities. Ratification of the European Charter for Regional and Minority Languages is a critical step towards the European Union's integration. Austria signed and ratified the Charter in 1992 and 2001, respectively. Slovenians, Croats, Hungarians, Czechs, Slovaks, and Roma are the six indigenous ethnic minorities recognized in Austria. Austria issued its fifth evaluation report in 2023. This report was reviewed by the researcher using critical discursive analysis. Based on the facts gathered, Austria is a country that should be emulated in terms of minority safeguarding and protection; nonetheless, changes are needed in several areas.

Резюме. Дослідження зосереджено на найважливіших питаннях мовної політики і законодавстві Австрії, які стосуються німецької мови як державної, та мов нацменшин. Конституція Австрії містить найважливіші положення щодо захисту німецької мови та мов нацменшин. Перші три статті Конституції Австрії є законодавчими актами, які мають вирішальне значення з точки зору захисту державної мови та мов нацменшин. Конституція Австрії передбачає захист і збереження етнічних спільнот. Далі в роботі досліджуються основні організації та адміністративні органи, які є відповідальними за розвиток сучасної австрійської мовної політики. В Австрії система захисту та підтримки мов нацменшин, як правило, добре розвинена. Австрія є активним учасником європейських програм, спрямованих на захист нацменшин. Ратифікація Європейської хартії регіональних мов і мов нацменшин є критичним кроком до інтеграції Європейського Союзу. Австрія підписала Хартію в 1992 році і ратифікувала її в 2001 році. В Австрії є шість визнаних корінних нацменшин: словенці, хорвати, угорці, чехи, словаки та роми. У 2023 році Австрія опублікувала свій п’ятий звіт про оцінку. Дослідник розглянув цей звіт за допомогою критичного дискурсивного аналізу. Виходячи зі зібраних фактів, Австрія є тою країною, з якої варто приклад щодо захисту та збереження нацменшин, однак у кількох сферах потрібні зміни.

A tanulmány Ausztria nyelvpolitikájára és jogszabályaira összpontosít, amelyek hatással vannak a német nyelvre mint államnyelvre, valamint a kisebbségi nyelvekre. Ausztria szövetségi alkotmánya tartalmazza a német és a kisebbségi nyelvek védelmét szolgáló legfontosabb rendelkezéseket. Az osztrák alkotmány első három cikkelye az államnyelv és a kisebbségi nyelvek védelmét szolgáló kulcsfontosságú jogszabályok. Az osztrák szövetségi alkotmány előírja az etnikai közösségek védelmét és megőrzését. A tanulmány a továbbiakban azokat az elsődleges szervezeteket és közigazgatási szerveket vizsgálja, amelyek a mai osztrák nyelvpolitika kialakulásáért felelősek. Ausztriában a kisebbségi nyelvek védelmének és támogatásának rendszere jellemzően jól kiépített. Ausztria aktív résztvevője a kisebbségek védelmét szolgáló európai programoknak. A Regionális és Kisebbségi Nyelvek Európai Kartájának ratifikálása meghatározó lépés az Európai Unióba való integrációja felé. Ausztria 1992-ben aláírta és 2001-ben ratifikálta a Kartát. A szlovének, horvátok, magyarok, csehek, szlovákok és romák a hat Ausztriában elismert őshonos etnikai kisebbség. Ausztria 2023-ban adta ki ötödik értékelő jelentését. Ezt a jelentést a kutató kritikai diskurzuselemzéssel vizsgálta felül. Az összegyűjtött tények alapján Ausztria a kisebbségvédelem és -megőrzés tekintetében egy olyan ország, amely példamutató, mindazonáltal több területen is változtatásokra van szükség.
Австрійська мовна політика щодо права на освіту рідною мовою
Az osztrák nyelvpolitika az anyanyelvi oktatáshoz fűződő jogok tekintetében
https://aab-philologica.kmf.uz.ua/aabp
Keywords: language policy; language policy in education; minorities; minority rights; minority rights in Austria; Austrian language policy